The pedagogical dimension in Pepetela's dramaturgy - Márcia Regina Rodrigues (Abril, 2016)
In this approach to Pepetela’s dramaturgy, produced in the social-political context of Angola in the post-independence period, we address its didactic and epic character that resembles Brecht’s theatrical proposition. The Angolan author goes from the professedly didactic play The rope (A corda, 1978) to a more effective implementation of the epic Brechtian assumptions in The revolt in the house of the idols (A revolta da casa dos ídolos, 1980), without discarding the pedagogical dimension in any of his plays. --- DOI: http://dx.doi.org/10.21881/abriluff.2016n17a358